Mandibular Reconstruction Using the Free Vascularized Fibula Graft: An Overview of Different Modifications - George Kokosis; Robin Schmitz; David B. Powers; Detlev Erdmann (Archives of Plastic Surgery, 2016)
The reconstruction of the mandible is a complex procedure because various cosmetic as well as functional challenges must be addressed, including mastication and oral competence. Many surgical techniques have been described to address these challenges, including non-vascularized bone grafts, vascularized bone grafts, and approaches related to tissue engineering. This review summarizes different modifications of the free vascularized fibula graft, which, since its introduction by Hidalgo in 1989, has become the first option for mandibular reconstruction. The fibula free flap can undergo various modifications according to the individual requirements of a particular reconstruction. Osteocutaneous flaps can be harvested for reconstruction of composite defects. 'Double-barreling' of the fibula can, for instance, enable enhanced aesthetic and functional results, as well as immediate one-stage osseointegrated dental implantation. Recently described preoperative virtual surgery planning to facilitate neomandible remodeling could guarantee good results. To conclude, the free fibula bone graft can currently be regarded as the "gold standard" for mandibular reconstruction in case of composite (inside and outside) oral cavity defects as well as a way of enabling the performance of one-stage dental implantation.